Proceso de atención de enfermería en recién nacido con sepsis bacteriana. - Morales Constante, Lisbeth Alexandra (2024)
The Spsis bacteria in neonates is knou as a serious infectious condition resulting from the entry of microorganisms into the bloodstream, the rapid action and efficient diagnosis contributes to improving the health of the patient, avoiding sequelae in the patient or mortality(Acuna Silva,2024). The present clinical case is about a male patient, newborn with a diagnosis of sepsis bacterial: son of a 38 year old mother, 4 months old, history of abortion and urinary tract infections. And leucorrea throughout the pregnancy. Patient was borna around 39 weeks of gestation by date of last menstrual period, obtained by cesarean section, Apgar of 7 at one minute and 8 at 5 minutes. Weight 3.000grams, size 50cm, head circumference 32c, abdominal circumference 31 cm, thermo regulation measure is given, clear liquid is aspirated, patency is checked, natural orífices. After 15 minutes of life, the neonate was transferred to a closed thermo cradle for thermoregulation, respiratory pattern and monitoring was evaluated, saturating 98%, accompanied by vomiting, generalized pallor and hypotension, for which reason hospitalización was decided X- rays and Ech were requested, ruling out intracranial lesions, edma and/or hemorrhages. Accompanied by test laboratory and blood cultures. Days later the infectious patient receives the first antimicrobial scheme (ampicillin plus gentamicin), due to maternal history. During his hospitalization the neonate evolves favorably so the attending physician decides to discharge him with stable vital signs and tests within normal parameters, and parents are educated about the care of their child at home.